2013
DOI: 10.3390/nu5061970
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Enhancing Resistant Starch in Ruminants Using Chemical Methods: Opportunities and Challenges

Abstract: High-producing ruminants are fed high amounts of cereal grains, at the expense of dietary fiber, to meet their high energy demands. Grains consist mainly of starch, which is easily degraded in the rumen by microbial glycosidases, providing energy for rapid growth of rumen microbes and short-chain fatty acids (SCFA) as the main energy source for the host. Yet, low dietary fiber contents and the rapid accumulation of SCFA lead to rumen disorders in cattle. The chemical processing of grains has become increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 100 publications
(170 reference statements)
0
48
0
1
Order By: Relevance
“…Substantial research efforts have been done over the years to modify starch degradation patterns in the rumen using various feed technological settings . We recently processed barley ( Hordeum vulgare L.), an important crop cereal used in ruminant nutrition worldwide, with various concentrations of lactic (LA) and tannic acid (TA) to modify its chemical composition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial research efforts have been done over the years to modify starch degradation patterns in the rumen using various feed technological settings . We recently processed barley ( Hordeum vulgare L.), an important crop cereal used in ruminant nutrition worldwide, with various concentrations of lactic (LA) and tannic acid (TA) to modify its chemical composition .…”
Section: Introductionmentioning
confidence: 99%
“…2 Substantial research efforts have been done over the years to modify starch degradation patterns in the rumen using various feed technological settings. 12 We recently processed barley (Hordeum vulgare L.), an important crop cereal used in ruminant…”
Section: Introductionmentioning
confidence: 99%
“…For example, in ruminants a large proportion of starch from feed grains is fermented by microorganisms in the rumen, but a substantial amount of starch can be digested in the small intestine or fermented in the large intestine . Thus dietary starch fractions may be termed by site of digestion as ruminal fermentable starch, ruminal bypass starch, undigestible starch, and ruminally resistant starch (RRS) . Research studies have examined ways to modulate the rumen degradability of starch, aiming to improve ruminant feed efficiency by changing the nature and amount of starch available to rumen microbiota, and/or shifting some starch digestion to the small intestine to improve its energetic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Deckardt et al (2013) concluded that the enhancement of dietary bypass starch promoted more net glucose being transferred from the small intestine to the liver. In the present study, both a heightened insulin level and a diminished glucagon level in the plasma of goats fed the HAS diet in response to an increased glucose supply would accelerate glycogenesis or force body cells to take up glucose from the blood, thus lessening blood glucose.…”
Section: Doi: 1017221/8666-cjasmentioning
confidence: 99%